GROWTH ANALYSIS OF HYBRID Eucalyptus urograndis (E-grandis x E. urophylla) IN RESPONSE TO SIMULATED DRIFT OF AUXINIC HERBICIDES - Carvalho, Gislean Pereira; Lemus Erasmo, Eduardo Andrea; Reis, Marcelo Rodrigues dos; Silvan, Girlanio Holanda [UNESP]; Silva, Andre Amaral da; Magnani Santos Alves, Patrick Callegari (Univ Federal Vicosa, 2018)
The aim of this study was to evaluate growth rates of E. urograndis under application of triclopyr and fluroxipyr+triclopyr herbicides. Was used a randomized block design with four replications in a factorial design (3x2x5), corresponding to herbicides (triclopyr and fluroxipyr+triclopyr), both with two doses (0.75 and 1.5% concentrations of 480 g and L-1 for triclopyr and 80+240 g and L-1 for fluroxipyr+triclopyr), plus one control (plants that did not receive herbicide application) and five evaluation dates at 15, 30, 45, 60 and 75 days after application (DAA). At 45 days after seedlings transplant, applications were performed with pressurized carbon dioxide backpack sprayer, equipped with beak tip (XR 110.02) with spray volume of 200 L ha(-1) and constant pressure of 35 kgf/cm(2) . Were evaluated: leaf area (LA), specific leaf area (SLA), leaf area ratio (LAR), leaf weight ratio (LWR), absolute growth ratio (AGR), relative growth ratio (RGR) and net assimilatory ratio (NAR). The drift of triclopyr and fluroxipyr + triclopyr herbicide in the hybrid E. urograndis affect plant development in the beginning of the establishment. At 75 days after simulation drift of herbicides the plants showed characteristics of the symptoms of intoxication. It's necessary to perform studies after 75 DAA to verify the complete recovery of the intoxication symptoms of E. urograndis hybrid plants resulting from the herbicide drift in the present study.
Keywords: Weed competition; Reforestation; Chemical control